2017
DOI: 10.1186/s12877-017-0411-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of left ventricular remodeling among elderly Asian women: a community-based cohort study

Abstract: BackgroundLeft ventricular (LV) remodeling is closely linked to the progression of heart failure. There are limited data on the epidemiology of new onset LV remodeling among elderly women, which requires further investigation.MethodWe examined data from a community-based cohort of women aged > 65 years, who had received > 2 echocardiography scans from 2009 to 2014. Exclusion criteria for patients included prior echocardiographic evidence of left ventricular enlargement (LVE) or hypertrophy (LVH). LVE was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Subjects with at least one of the following criteria in the serum lipid profile were recognized as hyperlipidemic: a total cholesterol (TC) level above 5.7 mmol/L, TG level above 5.7 mmol/L, HDL-C level below 0.8 mmol/L, and LDL-C level above 2.7 mmol/L [ 23 ]. The laboratory did not have any private information about the studied groups.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects with at least one of the following criteria in the serum lipid profile were recognized as hyperlipidemic: a total cholesterol (TC) level above 5.7 mmol/L, TG level above 5.7 mmol/L, HDL-C level below 0.8 mmol/L, and LDL-C level above 2.7 mmol/L [ 23 ]. The laboratory did not have any private information about the studied groups.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding dynamic balance, Paton et al [ 17 ] found no differences in dynamic balance using different insoles. Other research found no negative effects of insoles or small positive effects of different types of insoles on dynamic balance [ 35 , 36 ]. A reason for the difference between static and dynamic balance might be the sensory input during dynamic activities.…”
Section: Discussionmentioning
confidence: 99%
“…, 18 20 However, to our knowledge, the association between left ventricular mass index and low-density lipoprotein cholesterol concentration is first reported in children with masked hypertension. Recently, Wu et al, 21 in a longitudinal study, reported that low-density lipoprotein cholesterol concentration was predictive of the development of elevated left ventricular mass index among elderly women. Dyslipidaemia is recognised as a prominent risk factor for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%